Appropriateness of proton pump inhibitor use in patients admitted under the general medical unit. (9th July 2019) - Yap, Meng H.; Yip, Gary; Edwards, Alex; D'Intini, Vincent; Tong, Erica
Abstract: Background: Proton pump inhibitors (PPI) are extensively prescribed internationally and in Australia. However, minimal information is available on the appropriateness of PPI use in the general medical population. Aim: This study determined the proportion of general medical unit (GMU) inpatients taking a PPI on admission and evaluated the appropriateness of these PPI prescriptions. Methods: A single‐centre prospective observational study was conducted from 6 June to 11 July 2016. Consecutive patients were screened, and those taking a PPI prior to admission were included, whereas those not taking a PPI formed the control cohort. Appropriateness of PPI use was evaluated by: (1) reviewing for concordance with the Australian Therapeutic Guidelines and National Prescribing Service Guidelines on PPI use in gastro‐oesophageal reflux disease; (2) assessment of indication, dose and treatment duration by an expert panel consisting of two general physicians and one senior pharmacist. Results: Among 440 consecutive GMU patients, 198 (45.0%) were taking a PPI on admission. Of these, 66.2% had an inappropriate indication, dose or treatment duration. The largest category of inappropriate PPI use was excessive treatment duration (43.4%). In terms of comorbid conditions, PPI users had a higher prevalence of osteoporosis and/or history of fracture (42.9% vs 27.2%; p < 0.001) and hypomagnesaemia (10.6% vs 3.4%; p = 0.003). Conclusion: Inappropriate PPI use is highly prevalent among GMU inpatients. Given the potential for adverse effects, unnecessary health expenditure and pill burden, strategies should be developed to aid clinicians to consistently consider the utility of continuing long‐term PPI prescriptions in each patient's situation.